Applying Coaching Game Party by Using "Punctum" in Improving English Communicative Competence of Cadets at Barombong Merchant Marine Polytechnic - Fentry Hernaningsi Ruing; Eka Fatmawati Hading (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
The purpose of this research was to create the new method applied by Barombong Merchant Marine Polytechnic in achieving the academy's vision to produce professional and highly competitive sailors. The way to achieve this was by using a new method. The method used in this study was coaching game party by using "Punctum". This method was expected to be a breakthrough in conventional English teaching that seemed monotonous and boring. Generally, the steps conducted to gain the data from the cadets at Barombong Merchant Marine Polytechnic were : 1. Giving Pre-test on the first meeting. 2. Treatment: the cadets were treated by using punctum for 10 meetings. 3.Post Test on the 10th meeting. 4. Distributing the Questionnaire. and 5. Interviewing the cadets to support the result of post-test. The result of paired samples test with t-test indicated that the mean score was -2,86000, the standard deviation was 1,51052 and Standard Error Mean was 0,30210. It explained that the mean score gained by the cadets before getting the treatment was lower than after getting the treatment. The upper score was (-) 2,23649 and the lower score was (-) 3,48351 while the result of t-test was (-) 9,467. Therefore, the significance level = 0.05 was less than t-test (-) 9,467. The value of significance was 0.000 (divided by 2), it showed that: 0.000<0,025, so the null hypothesis (Ho) was rejected. According to the statistics theory if t-count > t-table, then Ho was rejected. In this case, the t-count was (-) 9,467 and the t-table was t = df, α/2 (24, 0025), t-table = 2,064 < t-count (-)9,467. So, the hypothesis (Ho) was rejected. It could be concluded that there was a significant difference between the test scores before and after applying coaching game party by using "punctum"as the treatment in the class.